"I Prefer to Stay Away": A Qualitative Study of Patients in an Opioid-Sparing Pain Management Protocol. Issue 4 (22nd April 2023) - Johnson, Emily; Yoshida, Maxwell; Hallway, Alexander; Byrnes, Mary; Waljee, Jennifer; Englesbe, Michael; Howard, Ryan
Abstract : Objective: The aim of this study was to explore beliefs and behaviors of opioid pain medications among patients undergoing elective surgery. Background: Opioid dependence after surgery is a major contributor to the ongoing opioid epidemic. Recent efforts by surgeons and health systems have sought to improve the education patients receive regarding safe opioid use after surgery; however, little is known about patients' pre-existing beliefs surrounding opioids. Methods: Semistructured interviews were conducted with patients who underwent 1 of 4 common elective surgical procedures at 1 institution. Patients were specifically asked about their knowledge and beliefs about opioids before surgery and their opinions of opioid-sparing recovery after surgery. Coding was conducted through iterative steps, beginning with an initial cycle of rapid analysis, followed by focused coding, and thematic analysis. Results: Twenty-one patients were interviewed. Three major themes emerged regarding patient opinions about using opioids after surgery. First, there was widespread awareness among patients about opioid medications, and preoperatively, patients had specific intentions about using opioids, often informed by this awareness. Second, patients described a spectrum of opioid related behavior which both aligned and conflicted with preoperative intentions. Third, there was tension among patients about opioid-free postoperative recovery, with patients expressing support, opposition, and emphasis on tailoring recovery to patient needs. Conclusions: Patients undergoing common surgical procedures often arrive at their surgical encounter with strong, pre-formed opinions about opioids. Eliciting these preexisting opinions may help surgeons better counsel patients about safe opioid use after surgery.